2022
DOI: 10.3390/molecules27134046
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrins and Metalloporphyrins Combined with N-Heterocyclic Carbene (NHC) Gold(I) Complexes for Photodynamic Therapy Application: What Is the Weight of the Heavy Atom Effect?

Abstract: The photophysical properties of two classes of porphyrins and metalloporphyrins linked to N-heterocyclic carbene (NHC) Au(I) complexes have been investigated by means of density functional theory and its time-dependent extension for their potential application in photodynamic therapy. For this purpose, the absorption spectra, the singlet–triplet energy gaps, and the spin–orbit coupling (SOC) constants have been determined. The obtained results show that all the studied compounds possess the appropriate propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Computational studies have been carried out on 3 a and 5 a to investigate the impact of the Au I cation and its position on the porphyrin ring on SOC of these systems. Calculation showed that, despite the expected heavy atom effect of gold, no particular changes of the SOC constant where observed in both cases due to the absence of involvement of the Au‐NHC fragments in the LUMO and LUMO+1 molecular orbitals [68] …”
Section: Gold‐based Complexes For Photo‐induced Anticancer Therapymentioning
confidence: 84%
See 1 more Smart Citation
“…Computational studies have been carried out on 3 a and 5 a to investigate the impact of the Au I cation and its position on the porphyrin ring on SOC of these systems. Calculation showed that, despite the expected heavy atom effect of gold, no particular changes of the SOC constant where observed in both cases due to the absence of involvement of the Au‐NHC fragments in the LUMO and LUMO+1 molecular orbitals [68] …”
Section: Gold‐based Complexes For Photo‐induced Anticancer Therapymentioning
confidence: 84%
“…Calculation showed that, despite the expected heavy atom effect of gold, no particular changes of the SOC constant where observed in both cases due to the absence of involvement of the Au-NHC fragments in the LUMO and LUMO + 1 molecular orbitals. [68] Boron-dipyrromethene (BODIPY) is another well studied class of organic fluorophores with a broad range of applications as fluorescent sensors (pH, metal ions, biomolecules,…) [69] or fluorescent probes for drug uptake studies and intracellular localization. [70] Moreover, BODIPY-based PDT photosensitizers are currently under intense investigation due to their high extinction coefficient, low dark toxicity, resistance to photobleaching and ease of photophysical properties modulation.…”
Section: Gold-based Complexes For Photo-induced Anticancer Therapymentioning
confidence: 99%
“…N-heterocyclic carbenes (NHCs) have been gaining research attention over years [ 1 ], as they tend to have great photosensitizing properties [ 2 , 3 ], due to their structural features [ 4 , 5 ]. The NHCs can form stable complexes and are therefore used in the development of photoactive molecular systems, which can then be applied in phototherapy (PT) [ 6 , 7 , 8 , 9 ]. PT has been shown to be quite effective and is commonly utilized in treating multiple bacterial and viral pathologies [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the experimental investigation of the chemical processes occurring after the administration of auranofin is very challenging due to the high chemical complexity impacted by this metallodrug either before or after its entry in the targeted cell. Nevertheless, the theoretical chemists have not yet succeeded in responding to this question either, despite numerous computational articles focused on the disentanglement of the mechanistic process of auranofin’s ligand exchange reactions [ 17 , 26 , 27 , 28 ]. Moreover, to the best of our knowledge, all the available computational studies of auranofin have addressed the behavior of one auranofin complex with its intended targets, for the sake of simplicity.…”
Section: Introductionmentioning
confidence: 99%